2022
DOI: 10.24042/jipfalbiruni.v11i1.10998
|View full text |Cite
|
Sign up to set email alerts
|

STEM education through PhET simulations: An effort to enhance students’ critical thinking skills

Abstract: One of the primary purposes of physics education is to help students develop critical thinking abilities to solve everyday situations. The purpose of this research is to investigate the impact of STEM education using PhET simulation on students' critical thinking skills. A pre-experimental approach with a one-group pre-test post-test design was used in this study. There were no control or comparator groups in this study, which was done in a single group. This study was carried out in a high school in Makassar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…STEM purposes of increasing critical thought ability, which prepare the students to become an innovator in the world. Therefore, they can answer the challenge to manage the 4.0 industry revolution such as big data (Khaeruddin & Bancong, 2022;Widayanti et al, 2019) (Milaturrahmah et al, 2017). The result of the research showed that the data of need analysis result done by the researcher could be identified that the development of e-module based on STEM integrated to PBL was very much needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…STEM purposes of increasing critical thought ability, which prepare the students to become an innovator in the world. Therefore, they can answer the challenge to manage the 4.0 industry revolution such as big data (Khaeruddin & Bancong, 2022;Widayanti et al, 2019) (Milaturrahmah et al, 2017). The result of the research showed that the data of need analysis result done by the researcher could be identified that the development of e-module based on STEM integrated to PBL was very much needed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of the e-module is performed systematically based on the related phases to result in helpful study material. Mathematics e-module development based on STEM, the analysis, the design, the development, the evaluation, and the revision must be developed (Khaeruddin & Bancong, 2022;Meishanti & Maknun, 2021;Sukendra et al, 2022). It is related to the ability to answer the questions in high critical thinking.…”
Section: Introductionmentioning
confidence: 99%
“…In 2022, integrating STEM into education to improve 4C skills, especially critical thinking skills, is a new trend among researchers, as conducted by (Khaeruddin & Bancong, 2022), which integrates STEM to improve critical thinking skills through a PhET simulator with results that show significant improvement. In the same year Rizkika et al (2022) developed STEM-based E-LKPD to improve learners' critical thinking skills.…”
Section: Introductionmentioning
confidence: 99%
“…Low mastery of concepts can cause students to experience difficulties in solving physics problems. The impact of low understanding and mastery of concepts can result in the inability of students to achieve a good level of creative thinking (Khaeruddin & Bancong, 2022).…”
Section: Introductionmentioning
confidence: 99%